"The People Who Leave Here Are Not the People Who Arrived.": A Qualitative Analysis of the Therapeutic Process and Identity Transition in the Offender Personality Disorder Pathway. (July 2023) - Blagden, Nicholas; Evans, Jacquie; Gould, Lloyd; Murphy, Naomi; Hamilton, Laura; Tolley, Chloe; Wardle, Kyra
Individuals with personality disorder are often construed as difficult to treat, and sometimes even "untreatable." In this study, 24 men who had completed treatment on the offender personality disorder treatment pathway participated in focus groups at a high-security prison in the United Kingdom. The results of the data analysis revealed three superordinate themes that captured the impact and experience of the therapeutic process. The three themes were "A self-reconstructed, " which focused on the reconstruing and reconstructions of participants' identity and how intervention assisted with a coherent narrative of self. The second superordinate theme, "Relational resilience and dealing with abandonment, " relates to the attachment to therapists and the negotiation of relational boundaries and resilience. The third theme, "Reimagining and re-experiencing trauma, " focuses on participants' exploration and reliving of trauma, and how group processes allowed for shared understanding and a reconstruing of their trauma. Implications for policy and practice are discussed.